Draft Genome Sequence of Frankia sp. Strain BMG5.23, a Salt-Tolerant Nitrogen-Fixing Actinobacterium Isolated from the Root Nodules of Casuarina glauca Grown in Tunisia - Ghodhbane-Gtari, Faten (American Society for Microbiology, 2014)
Nitrogen-fixing actinobacteria of the genus Frankia are symbionts of woody dicotyledonous plants termed actinorhizal plants. We report here a 5.27-Mbp draft genome sequence for Frankia sp. strain BMG5.23, a salt-tolerant nitrogen-fixing actinobacterium isolated from root nodules of Casuarina glauca collected in Tunisia.